Review of the generic level classification of New World Mantispidae (Neuroptera) - Norman D. Penny (Acta Amazonica, 1982)
Abstract The higher classification of New World Mantispidae is reviewed. Keys are provided to subfamilies, tribes and genera for the New World. The genus Fusa is synonomized with Gerstaeckerella, Nobrega with Climaciella, Bellarminus with Nolima; Anchieta is resurrected. The genus Mantispa is divided into four species groups, and the genus Entanoneura is redefined.